Effects of ball-milling on physicochemical, thermal and functional properties of extruded chickpea (Cicer arietinum L.) powder. Issue 1 (1st January 2019) - Raza, Husnain; Ameer, Kashif; Zaaboul, Farah; Sharif, Hafiz Rizwan; Ali, Barkat; Shoaib, Muhammad; Akhtar, Wasim; Zhang, Lianfu
ABSTRACT: The objective of this study was to explore and compare the effects of particle size distribution (PSD) on physicochemical, functional thermal and structural properties of extruded (ECP) and raw (RCP) chickpeas powders. Chickpea powders were obtained by flour fractionating through standard sieves of various particle sizes: 80, 120, 160, and 200 mesh (<180, <125, <95, and <75 µm). Extrusion achieved a desirable degree of lightness in finest (ECP 200) powder followed by increases of yellowness and redness as compared to the finest fraction of control samples (RCP 200). The results of TGA showed better stability for ECP at 600°C with reduced particle sizes as compared to RCP at 400°C. The results of FTIR and XRD showed differences in band intensities and crystalline structures of samples. Extrusion caused microstructural changes in ECP which were elucidated by SEM. ECP exhibited higher WAC ranged from 2.80–2.71 g/g compared to RCP (1.87–1.81 g/g).